Comment on “TTM protocol may benefit outcomes in cardiac arrest survivors” - Ko, Tzu-Chien; Hsieh, Chien-Chieh; Jaw, Fu-Shan; Chang, Chang-Chen; Su, Mei-Chin (The American journal of emergency medicine, 2025)
[ 1] titled “The compliance with TTM protocol may benefit outcomes in cardiac arrest survivors: A retrospective cohort study.” The research demonstrated that non-traumatic cardiac arrest survivors who did not undergo targeted temperature management (TTM) following the protocol had worse neurological outcomes compared to the protocol-compliant group. Investigating adjunctive strategies such as neuromuscular blockers for precise temperature control and enhance temperature stability [ 10], automated feedback devices for minimizing variability [ 11], and the broader role of protocolized post-cardiac arrest care could further optimize outcomes.